305 Engine exhaust exposure and lung cancer risk in farming. (11th October 2013) - Tual, S; Silverman,; Koutros, S; Blair,; Sandler,; Lebailly,; Andreotti,; Hoppin,; Freeman, Beane
Abstract : Objectives: Farmers have lower lung cancer rates than the general population, due to lower rates of smoking and possibly exposure to endotoxins. Farmers do, however, have exposure to potential lung carcinogens such as diesel exhaust from the operation of diesel-powered equipment. Using data from the Agricultural Health Study (AHS), a US-based prospective cohort study, we evaluated the risk of incident lung cancer from enrollment (1993–1997) to 2008 in relation to farm equipment use. Methods. Information on farm equipment use was obtained by self-report at study enrollment. There were 233 lung cancers among male farmers and 133 among spouses. Relative risks (RR) were estimated using Poisson regression controlling for lifestyle (including smoking) and agricultural factors. Analyses were stratified by exposure to other agricultural exposures and histological subtypes. Results. Overall, there was no significant association between any type of farm equipment and lung cancer risk but we observed a nonsignificant effect of daily driving diesel tractors for adenocarcinomas (RR = 1.95, 95% CI:0.92–4.10). A significant interaction between driving diesel tractors and exposure to animals was also observed for this subtype in farmers (nonexposed to animals: RR = 5.75, 95% CI:2.17–15.28, exposed: RR = 0.94, 95% CI:0.34–2.57, p-interaction = 0.04). A similar effect modification for driving diesel tractors was observed in spouses for lung cancer overall (nonexposed to animals: RR(≥monthly vs less than monthly) = 2.25, 95% CI:1.15–4.43, exposed: RR = 0.42, 95% CI:0.15–1.20, p-interaction = 0.01). Although the interaction was nonsignificant for adenocarcinomas in spouses (p = 0.37), the magnitude of risk was similar (nonexposed to animals: RR = 2.77, 95% CI: 1.05–7.31). Conclusion. These findings suggest that use of diesel-powered farm equipment may increase lung cancer risk in people working in agricultural settings among those not exposed to animals, exposure that has been previously inversely related to lung cancer risk, possibly due to endotoxins. Further efforts are needed to refine the exposure assessment for diesel exhaust fumes in low and chronically exposed populations.